The Costs of Closing Failed Banks: A Structural Estimation of Regulatory Incentives - Kang, Ari; Lowery, Richard; Wardlaw, Malcolm (Review of Financial Studies, 2015)
We estimate a dynamic model of the decision to close a troubled bank. Regulators trade off an aversion to closing banks against the risk that allowing a bank to continue will raise the eventual costs to the deposit insurance fund. Using a conditional choice probability approach, we estimate the costs associated with closing banks, both in direct costs to the insurance fund and in other costs perceived by regulators, either social or personal. We find that delayed closures were driven by a desire to defer costs, an aversion to closing the largest and smallest troubled banks, and political influence.